Assessment of Reliability of Quality Control of Building Materials - Loganina Valentina Ivanovna; Zaytseva Maria Vladimirovna (New Approaches in Engineering Research Vol. 1, 2021)
The goal of this project is to evaluate the quality control of construction materials, taking into consideration measurement error, the status of the technical process of product manufacturing, control completeness, and quality indicator variability. Data on influence of an error of measurement on probability of decision-making about acceptance of production are resulted at statistical instability of process of manufacture. On the basis of the example of brick manufacture, it is demonstrated that accepting a batch of bricks while accounting for measurement error in an unstable production process may be incorrect. It is feasible to enhance the dependability of product quality control and eliminate mistakes in rejecting items by using a statistically stable and reproducible method. Information about the results of calculating the reliability of quality control of dry building mixes, based on the requirements of regulatory documents, is provided. The block diagram of the control reliability is considered. It is shown that the normative security of the quality of dry construction mixtures is 0.9447957, which implies a probability of a defect 5.52%. To ensure a higher level of dry building mixtures quality, the application of the six sigma methodology is proposed. The information on evaluating the sample’s representativeness in establishing the quality of construction materials is provided. The difference between the number of samples given in the normative standards for test methods and the computed data, taking into consideration the values for standard confidence probabilities, supplier and consumer risk, is demonstrated. The methodology of quality control of building materials is considered taking into account the indicator of completeness of control.